Technical aspects of neuraxial analgesia during labor and maternity care: an updated overview - Antonio Coviello; Carmine Iacovazzo; Maria Grazia Frigo; Marilena Ianniello; Dario Cirillo; Giuseppe Tierno; Andrea Uriel de Siena; Pasquale Buonanno; Giuseppe Servillo (Journal of Anesthesia, Analgesia and Critical Care)
Abstract Labor analgesia is increasingly widespread throughout the world with a rate ranging from 10 to 60%. The benefits regarding clinical and non-clinical maternal–fetal outcomes are currently discussed in international scientific literature. Even stage of labor needs a different and appropriate approach to control the pain; however, different techniques are reported in literature. The following study intends to give a brief overview of the characteristics of the different neuraxial and non-neuraxial techniques currently available and the non-technical skills necessary for effective assistance to pregnant women, providing insights on the topic to understand critical issues at the same time. After bibliographic research since 2018 to 2023, many randomized controlled trials, literature reviews, systematic reviews, and metanalysis were evaluated to create this brief overview. The following pharmacological and non-pharmacological approaches were assessed: spinal techniques, such as epidural analgesia (EA), combined spinal-epidural (CSE), dural puncture epidural (DPE), and continuous spinal anesthesia (CSA); pharmacological administration of nitrous oxide (N2O) and systemic opioids (morphine, fentanyl, and pethidine); as the third one transcutaneous electric nerve stimulation (TENS), acupressure/acupuncture, aromatherapy, and breathing exercises. All the assessed approaches are relatively safe and effective, but the association of technical and non-technical skills is needed to improve the maternal and fetus outcome. More studies are needed to clarify what is the best approach to labor analgesia.